Use of Alternative Communication Systems I-Talk to Improve Cerebral Palsy Communication Skills - Dewi, Nurul Huda Fitriani; Susetyo, Budi; Rochyadi, Endang (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2021)
The background of this study was students with Cerebral Palsy who had difficulty speaking. As a result of the stiffness of the muscles, the speech organs cause the messages conveyed verbally by the child to be difficult to understand the communicant. This study aims to develop a system of Alternative and Augmentative Communication (AAC) and to know its influence on subject communication skills. The research method used is a mixed-method with a sequential exploratory approach. The results of this study are an alternative I-Talk communication system and improvement of subject communication skills. Improved communication skills can be seen from the communication skills of the subject which at the beginning could not be understood at all by the communicant, after using I-Talk increased with the indicator being able to call parents, caregivers, and teachers. Furthermore, the subject can convey wishes when wants to drink, snack, eat, and others.